Produktivitas Tenaga Kerja Pada Usahatani Ubi Jalar di Desa Lenganeng Kecamatan Tabukan Utara Kabupaten Kepulauan Sangihe - Chrisye Limpong Amelia Limpong; Eyverson Ruauw; Charles R. Ngangi; Martha M. Sendow (Universitas Sam Ratulangi, 2014)
ABSTRACTChrisye Amelia Limpong Labor Productifity of Sweet Potato Farming at Lenganeng Vilage Northern Tabukan Sub District Under the quidance of Eyverson Ruauw as a Chairman, Charles R. Ngangi and Martha M. Sendow as members.The objective of this research is to know the labour prductivity of sweet potatos farming at Lenganeng Villages North Sub District. Tabukan district. This study uses case study method of sweet potato farming at Lenganeng Villages North Tabukan sub district.Data collection is conducted through direct interview, with Farmer group and individual using simple random sampling method. Samples taken from farmer group andindividual 16 respondents The data collected will be analysed descriptively.The result of this research showed that labor productivity of sweet potatos farm in Lenganeng villages Northern Tabukan Sub District according the amount of labor used was 79,72 kg per labor, product`ivity according to the number of working hours (working day) was 57,66 kg and labor productivity according working day hour (HOK) was 35,89 kg per HOK.The condusson of this researched, if the sweet potato farmers in the village lenganeng village use more people working on the land, would be more effective than using less to work more days, because the value of the average productivity by the amount of labor more than the value of the average labor productivity by the number of working day.